Day-of-the-week effect: Petroleum and petroleum products - Andrew C. Meek; Seth A. Hoelscher (Cogent Economics & Finance, 2023)
This study tests for calendar anomalies in returns for petroleum and petroleum products via the futures market, specifically, the day-of-the-week (DOW) effect. The energy future contracts in this study are the WTI (West Texas Intermediate), Brent, RBOB (Reformulated Blendstock for Oxygenate Blending) Gasoline, Heating Oil, and Natural Gas. Futures provide a more liquid insight into price movements relative to spot prices, where financial market participants can engage. We ensure the most appropriate price is used by focusing on the most liquid contracts by combining the front two months of the studied commodities nearing expiration. Our research shows that the DOW effect varies across the respective energy commodities; however, for investors engaged in trading these futures, our results may help time their trade decisions.
Keywords: G11; G12; G14; L71; Q02; Q40; 330; calendar anomalies; Day-of-the-week effect; EGARCH; EMH; GARCH; petroleum products; PGARCH; QGARCH; TGARCH